Hymenopterous parasites of Phthorimaea operculella - Borges, Jácomo Divino; Carneiro, Maurízia de Fátima; Almeida, Armando Antunes de (Pesquisa Agropecuaria Brasileira, 2014)
This paper deals with a survey for hymenopterous parasitas of Phthorimaea operculella in the municipality of Guitandinha, State of Paraná, Brazil. The parasites were identified as: Apanteles subandinus Blanchard, 1947 (Braconidae); Arrenoclavus koehleri (Blanchard, 1940) (Encyrtidae); Campoplex haywardi Blanchard, 1946 (Ichneumonidae) and Campoletis grioti (Blanchard, 1946) (Ichneumonidae). The first two parasites were the most frequent ones, with a percentage of occurrence of 42.2 and 38.8, respectively.
Keywords: Apanteles subandinus; Arrenoclavus koehleri; Campoplex haywardi; Campoletis griori